2012
DOI: 10.1371/journal.pone.0051426
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Mechanism of Mutant p53 Stabilization: The Role of HSP70 and MDM2

Abstract: Numerous p53 missense mutations possess gain-of-function activities. Studies in mouse models have demonstrated that the stabilization of p53 R172H (R175H in human) mutant protein, by currently unknown factors, is a prerequisite for its oncogenic gain-of-function phenotype such as tumour progression and metastasis. Here we show that MDM2-dependent ubiquitination and degradation of p53 R175H mutant protein in mouse embryonic fibroblasts is partially inhibited by increasing concentration of heat shock protein 70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 84 publications
(76 reference statements)
6
105
0
1
Order By: Relevance
“…It has recently been shown that mutant p53 proteins may form amyloid-like aggregates in cancer cells (Ano Bom et al 2012), and the ubiquitination and proteasomal degradation of mutant p53 is inhibited by chaperone proteins that promote their aggregation (Wiech et al 2012). Since different alleles of mutant p53 showed a different propensity to form amyloid-like structures (Ano Bom et al 2012), we hypothesize that the aggregation of mutant p53 may show allele specificity, which may affect its ubiquitination.…”
Section: Susceptibility To Ubiquitination Determines the Degradation mentioning
confidence: 76%
See 1 more Smart Citation
“…It has recently been shown that mutant p53 proteins may form amyloid-like aggregates in cancer cells (Ano Bom et al 2012), and the ubiquitination and proteasomal degradation of mutant p53 is inhibited by chaperone proteins that promote their aggregation (Wiech et al 2012). Since different alleles of mutant p53 showed a different propensity to form amyloid-like structures (Ano Bom et al 2012), we hypothesize that the aggregation of mutant p53 may show allele specificity, which may affect its ubiquitination.…”
Section: Susceptibility To Ubiquitination Determines the Degradation mentioning
confidence: 76%
“…In addition, mutant p53 has been reported to misfold and form amyloid oligomers and fibrils (Ano Bom et al 2012), which might be intrinsically resistant to proteasomal degradation. Indeed, interaction of mutant p53 with chaperone proteins such as Hsp70 has been shown to inhibit its ubiquitination, mediated by MDM2 and proteasomal degradation, and promote its aggregation (Wiech et al 2012). Thus, how to effectively promote the degradation of mutant p53 in cancer cells is an important question to be investigated.…”
mentioning
confidence: 99%
“…There are many examples in the literature supporting this idea. For example, p53 and mutants of this protein are protected from degradation in the presence of excess HSP70 (50). In addition, human ether-a-go-go-related gene, a subunit of the potassium current I protein, is stabilized when HSP70 is overexpressed (51).…”
Section: Discussionmentioning
confidence: 99%
“…(2) MDM2 and HSP70 might stabilize mutant p53 by forming structures named "pseudo-aggregates," which can be involved in p53 intracellular aggregation. 71 (3) The co-aggregation of p53 with its partalogs, p63 and p73, has been described by Xu et al 9 (4) p53 displays prionoid characteristics, since mutp53 aggregates are able to induce wTp53 conversion to the misfolded, aggregation-prone conformation. 8 These p53 aggregates might be captured by other cells through macropinocitosis.…”
Section: P53 Aggregation and Its Prion-like Effectmentioning
confidence: 99%
“…69,70 Certain interactions have been proposed to stabilize p53 mutants in cells. The transient but recurrent interaction between p53 and the cellular chaperone HSP70 (Heat-Shock Protein 70) may promote an increase in the half-life of mutant p53 protein; in addition, in the presence of MDM2, these "pseudoaggregates" can form stable amyloid-like structures 71 that appear to be associated with an altered structural conformation of p53.…”
Section: Molecular Partners Involved In P53 Aggregationmentioning
confidence: 99%